2015
DOI: 10.1016/j.apmr.2014.07.419
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Inter-Hemispheric Imbalance Using Imaging and Noninvasive Brain Stimulation in Patients With Chronic Stroke

Abstract: OBJECTIVE To determine how inter-hemispheric balance in stroke, measured using transcranial magnetic stimulation (TMS), relates to balance defined using neuroimaging (functional magnetic resonance (fMRI) and diffusion tensor imaging (DTI)), and how these metrics of balance are associated with clinical measures of upper limb function and disability. DESIGN Cross-Sectional SETTING Clinical Research Laboratory PARTICIPANTS Ten chronic stroke patients (63±9 years) in a population based sample with unilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 50 publications
2
70
0
2
Order By: Relevance
“…Total scan time was 12 minutes. (Cunningham et al, 2015a). Acquisition provided whole-brain coverage using 2-mm isotropic voxels (field of view: 256 × 256 mm, image matrix: 128 × 128 and 52 2-mm-thick slices).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total scan time was 12 minutes. (Cunningham et al, 2015a). Acquisition provided whole-brain coverage using 2-mm isotropic voxels (field of view: 256 × 256 mm, image matrix: 128 × 128 and 52 2-mm-thick slices).…”
Section: Methodsmentioning
confidence: 99%
“…Functional MRI (fMRI) activation was used for stereotactic guidance of TMS (Brainsight, Rogue Research Inc., Montreal, QC, Canada) (Cunningham et al, 2015a). FMRI guidance is helpful because patients with chronic stroke undergo cortical reorganization (Lotze et al, 2003, Ward et al, 2003a, Ward et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…There is evidence that PLIC and CR were mainly comprised of CST which project from the motor cortex to the PLIC [34, 36, 37] and to brain stem [33]. Previous diffusion microstructural studies have showed significantly decreased FA values in ipsilesional [5, 38, 39] and contralesional [24, 40] PLIC and CST after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Still, to open these lines of discussion so a more strategic investigation of these factors can be conducted in various populations, we present the this supplement which provides data based papers and reviews discussing state of the art clinical and research application and considerations for non-invasive brain stimulation targeting a variety of neurorehabilitative diagnoses and impairments. Featured articles include the following: Cunningham et al 40 discuss the potential utility of neuro-navigated TMS in revealing mechanisms of functional motor recovery in chronic stroke. In comparing its use to state-of-the-art imaging- functional MRI and Diffusion Tensor Imaging (DTI)- they discuss how its neurophysiologic measurements relate to inter-hemispheric balance, and reveal adaptations to damaged output from stroke hemisphere.…”
Section: What Is Non-invasive Brain Stimulation?mentioning
confidence: 99%
“…Cunningham et al 40 discuss the potential utility of neuro-navigated TMS in revealing mechanisms of functional motor recovery in chronic stroke. In comparing its use to state-of-the-art imaging- functional MRI and Diffusion Tensor Imaging (DTI)- they discuss how its neurophysiologic measurements relate to inter-hemispheric balance, and reveal adaptations to damaged output from stroke hemisphere.…”
Section: What Is Non-invasive Brain Stimulation?mentioning
confidence: 99%